DAMPAK PENERAPAN PERKULIAHAN DARING TERHADAP MATA KULIAH PRAKTEK RIAS PENGANTIN DI AKS – AKK YOGYAKARTA - Herina Yuwati; Triwarsi Hapsari (Jurnal Socia Akademika, 2021)
This research aims to find out how far the impact of online lectures on the practice of Bride and Grooming at AKS-AKK Yogyakarta is. This research includes descriptive types of research and uses descriptive analysis. In this study, the determination of research subjects was determined by sampling techniques. While the object examined is the impact of online lectures on makeup practice courses. Panelists as many as 48 people, students of the study program cosmetology semester IV and VI. Data collection is done with interviews, observations, and documentation. Interviews and observations are used to obtain detailed data about the impact of online lectures on the practice of Bridal Makeup. At the same time, the documentation is used to illustrate the primary form of the effect of the online class. The data is analyzed with descriptive analysis techniques. The analysis results showed that the impact of online lectures on practical courses significantly affects students' competence, so the results cannot be maximized as expected.